2016
DOI: 10.1111/ecog.02378
|View full text |Cite
|
Sign up to set email alerts
|

Spatial extinction or persistence: landscape‐temperature interactions perturb predator–prey dynamics

Abstract: Recognising that species interact across a range of spatial scales, we explore how landscape structure interacts with temperature to influence persistence. Specifically, we recognise that few studies indicate thermal shifts as the proximal cause of species extinctions; rather, species interactions exacerbated by temperature result in extinctions. Using microcosm‐based experiments, as models of larger landscape processes, we test hypotheses that would be problematic to address through field work. A text‐book pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…In our study, both predator and prey populations went deterministically extinct by the end of the experiment at all temperatures, consistent with the typical behavior of Didinium and Paramecium without stabilizing environmental factors introduced to the microcosms (Luckinbill, 1973;DeLong & Vasseur, 2013;Salt et al, 2017). Although extinctions occurred earlier in warmer temperatures, the system did not undergo major qualitative shifts such as from stable to unstable or from having a fixed point equilibrium to having oscillations, which are common predictions from theory (Vasseur & McCann, 2005;Amarasekare, 2015).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In our study, both predator and prey populations went deterministically extinct by the end of the experiment at all temperatures, consistent with the typical behavior of Didinium and Paramecium without stabilizing environmental factors introduced to the microcosms (Luckinbill, 1973;DeLong & Vasseur, 2013;Salt et al, 2017). Although extinctions occurred earlier in warmer temperatures, the system did not undergo major qualitative shifts such as from stable to unstable or from having a fixed point equilibrium to having oscillations, which are common predictions from theory (Vasseur & McCann, 2005;Amarasekare, 2015).…”
Section: Discussionsupporting
confidence: 86%
“…Full-size  DOI: 10.7717/peerj.9377/ fig-4 period and amplitude of Didinium-Paramecium caudatum dynamics (Salt et al, 2017). Yet by considering a broad range of temperatures, we also found that some of these dynamic shifts themselves may be unimodal rather than monotonically changing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, temperature-induced increases in functional connectivity could increase diversity at both local and regional scales within metacommunities (Cadotte & Fukami, 2005;Verreydt et al, 2012). Although previous experiments investigating the effect of warming on metacommunity dynamics have maintained tractability by warming local patches while manipulating dispersal rates (Limberger, Low-D ecarie, & Fussmann, 2014;Thompson et al, 2015), allowing warming to simultaneously alter both local species interactions and species' movement between patches would provide a critical next step toward understanding the full impact of warming in spatially structured environments (Salt, Bulit, Zhang, Qi, & Montagnes, 2016).…”
mentioning
confidence: 99%
“…food saturated on suitable prey) at 18 °C, for each species. Data were obtained from a various sources at a range of temperatures[59][60][61][62][63][64][65][66] and were converted to rates at 18 °C by two methods, either assuming a Q10 of 2 or that growth rate varies linearly with temperature at a rate of 0.07 r (d -1 ) °C -1[67].…”
mentioning
confidence: 99%